2011
DOI: 10.3858/emm.2011.43.6.041
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes involved in innate immunity and susceptibility to benzene-induced hematotoxicity

Abstract: Benzene, a recognized hematotoxicant and carcinogen, can damage the human immune system. We studied the association between single nucleotide polymorphisms (SNPs) in genes involved in innate immunity and benzene hematotoxicity in a cross-sectional study of workers exposed to benzene (250 workers and 140 controls). A total of 1,236 tag SNPs in 149 gene regions of six pathways were included in the analysis. Six gene regions were significant for their association with white blood cell (WBC) counts (MBP, VCAM1, AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We have applied candidate gene‐association studies to study susceptibility to benzene and formaldehyde toxicity. We, along with others, identified associations between genetic polymorphisms in genes encoding specific metabolic enzymes, cytokines, DNA repair and genomic maintenance proteins, and cellular adhesion proteins with known or potential roles in niche function and innate immunity, and increased susceptibility to benzene‐induced hematotoxicity. Information on individual susceptibility to formaldehyde is currently limited.…”
Section: Functional Genomics Screening Methods To Study Genetic Suscementioning
confidence: 86%
“…We have applied candidate gene‐association studies to study susceptibility to benzene and formaldehyde toxicity. We, along with others, identified associations between genetic polymorphisms in genes encoding specific metabolic enzymes, cytokines, DNA repair and genomic maintenance proteins, and cellular adhesion proteins with known or potential roles in niche function and innate immunity, and increased susceptibility to benzene‐induced hematotoxicity. Information on individual susceptibility to formaldehyde is currently limited.…”
Section: Functional Genomics Screening Methods To Study Genetic Suscementioning
confidence: 86%
“…Therefore, genetic variation in MBP resulting in differential expression of MBP protein could influence the immune response by either enhancing or inhibiting T-cell activation. A previous study that examined polymorphisms in genes involved in innate immunity and susceptibility to benzene-induced hematotoxcity indicated that variation in the MBP gene was significantly associated with white blood cells counts [Shen et al, 2011]. Several studies have also indicated that MBP is associated with cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…Under conditions prevailing at the workplace, benzene is absorbed by inhalation, although dermal absorption of liquid benzene is also significant [2]. Benzene metabolism has been extensively studied in various animal models, in vitro incubations, and by theoretical calculations [2][3][4][5][6][7], with evidences that it is impossible to distinguish between occupational and environmental exposure when the benzene level in the workplace is less than 100 μg/m 3 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated skin contact can cause redness, blistering, and scaly dermatitis [2,4,5]. Recent studies showed significant hematological disorders, chromosomal aberrations as well as relatively high concentration of phenol in 24-hour urine samples due to exposure to benzene in chemical industry workers [4][5][6][7]. Furthermore, blood disorders may lead to anemia and other diseases causing a significant reduction in working capacity and activity of workers, loss of working hours, and the increase in the costs of medical care of the affected workers [4].…”
Section: Introductionmentioning
confidence: 99%